A Study of 'Kenry' in Japanese and 'Hak' in Indonesian - . Azhar; Matsumura Yoshiyuki (Humaniora, 2010)
This research basically aims at exploring the word 'kenry' (in Japanese) and 'hak' (in Indonesian). This study also attempts to compare the views of the Japanese towards the word 'kenry' and the Indonesian towards the word 'hak'. The research findings indicate that the understanding of the Japanese towards the concept of 'hak' has some contradictions in connection with the consideration of relation between the people and society. This indicates that right and consideration of the human relation is a very different thing in Japan. In Indonesia, on the other hand, the statement of right, consideration to the weak, and consideration of the human relation is regarded as a factor with is not contradictory to one another.